Pembuatan Mading sebagai Upaya Pencegahan Bullying Terhadap Peserta Didik di SD Muhammadiyah IV Pekanbaru - Tiara Sahana, Rossy; Putra, Ilham Abhista; Sholihat, Neng (LPPM UMRI, 2025)
Bullying is one of the serious problems that occur in the school environment and can have a negative impact on the social and emotional development of students. This study aims to analyze the effectiveness of mading as an educational medium in efforts to prevent bullying in SD Muhammadiyah IV Pekanbaru. The method used is qualitative descriptive with a participatory approach, where KKN-DIK students not only observe the phenomenon of bullying, but also participate in prevention activities through making mading. The data used in this study consisted of primary data and secondary data. The data collection technique in this study was carried out by observation to see student interactions before and after the presence of mading, interviews with students and teachers to evaluate the understanding and effectiveness of mading, as well as documentation in the form of photos and videos as evidence of program implementation. The research findings show that bulletin boards are effective in increasing students' awareness about bullying, helping them better understand its forms, impacts, and ways to prevent it.